Exploring providers' perspectives of a community based TB approach in Southern Ethiopia: implication for community based approaches. Issue 1 (June 2015) - Datiko, Daniel; Yassin, Mohammed; Tulloch, Olivia; Asnake, Girum; Tesema, Tadesse; Jamal, Habiba; Markos, Paulos; Cuevas, Luis; Theobald, Sally
Abstract Background There is increasing interest in the role of close-to-community providers in supporting universal health coverage, but questions remain about the best approaches to supporting and motivating these providers, and the optimal package they can deliver indifferent contexts and support required. We report on the experiences of different health providers involved in a community based intervention to support access to tuberculosis diagnosis and treatment in Southern Ethiopia. Methods The aim of the study is to explore the experiences of health providers in delivering a community-based tuberculosis package in southern Ethiopia and to draw lessons for community-based programmes. A qualitative methodology was used. Methods included in-depth interviews (IDIs, n= 37) with all health provider groups: Community health promoters (CHPs), health extension workers (HEWs), district supervisors and laboratory technicians were undertaken to obtain a detailed understanding of the experiences of providers in the community based tuberculosis package. These were complemented with cadre specific focus group discussions (n= 3). We used the framework approach for qualitative analysis. Results The key theme that emerged was the positive impact the community-based intervention had on vulnerable groups' access to diagnosis, care and treatment for tuberculosis. Providers found the positive feedback from, and visible impact on, communities very motivating. Other themes related to motivation and performance included supervision and support; learning new skills; team problem solving/ addressing challenges and incentives. Against the backdrop of the Ethiopian Health Extension Programme (HEP), HEWs were successfully able to take on new tasks (collecting sputum and preparing smears) with additional training and appropriate support from supervisors, laboratory technicians and CHPs. Conclusion All categories of providers were motivated by the high visible impact of the community-based intervention on poor and vulnerable communities and households. HEWs role in the community-based intervention was supported and facilitated through the structures and processes established within the community-based intervention and the broader nation-wide Health Extension Programme. Within community based approaches there is need to develop context embedded strategies to support, sustain and motivate this critical cadre who play a pivotal role in linking health systems and rural communities.